Cryo-electron tomography of microtubule-kinesin motor complexes - Cope, Julia (2009)
Microtubules complexed with molecular motors of the kinesin family or non-motor microtubule associated proteins (MAPs) such as tau or EB1 have been the subject of cryo-electron microcopy based 3-D studies for several years. Most of these studies that targeted complexes with intact microtubules have been carried out by helical 3-D reconstruction, while few were analyzed by single particle approaches or from 2-D crystalline arrays. Helical reconstruction of microtubule-MAP or motor complexes has been extremely successful but by definition, all helical 3-D reconstruction attempts require perfectly helical assemblies, which present a serious limitation and confine the attempts to 15- or 16-protofilament microtubules, microtubule configurations that are very rare in nature. The rise of cryo-electron tomography within the last few years has now opened a new avenue towards solving 3-D structures of microtubule-MAP complexes that do not form helical assemblies, most importantly for the subject here, all microtubules that exhibit a lattice seam. In addition, not all motor domains or MAPs decorate the microtubule surface regularly enough to match the underlying microtubule lattice, or they adopt conformations that deviate from helical symmetry. Here we demonstrate the power and limitation of cryo-electron tomography using two kinesin motor domains, the monomeric Eg5 motor domain, and the heterodimeric Kar3Vik1 motor. We show here that tomography does not exclude the possibility of post-tomographic averaging when identical subvolumes can be extracted from tomograms and in both cases we were able to reconstruct 3-D maps of conformations that are not possible to obtain using helical or other averaging-based methods.